Comparative Characteristics of Beta-Blockers in Patients with Congenital Long QT Syndrome - A. Yu. Proshlyakov; P. Sh. Chomakhidze; N. A. Novikova (Рациональная фармакотерапия в кардиологии)
Congenital long QT syndrome is a pathology that requires special attention and knowledge about the safety and effectiveness of various medications. Prolongation of the QT interval due to congenital or acquired causes is an important factor in the development of an unfavorable life forecast with the formation of an elongated QT syndrome. With an unfavorable course, patients suffer from loss of consciousness, episodes of tachycardia. Often, stable polymorphic ventricular tachycardia develops. The risk of sudden cardiac death in this pathology can vary from 0.33% to 5%. In people who have suffered an episode of cardiac arrest, and do not have a permanent prescribed antiarrhythmic therapy, the mortality rate reaches 50% within 15 years. Preventive administration of antiarrhythmic drugs is not always effective. A positive result of treatment depends on the severity of long QT syndrome and its genotype. Beta-blockers are often prescribed to patients of different ages with various cardiac pathologies, including for the prevention of arrhythmia in long QT syndrome. Beta-blockers differ in various pharmacokinetic and pharmacodynamic parameters (lipophilicity/hydrophilicity, selectivity, presence/absence of internal sympathomimetic activity), which, along with the variant of the disease genotype, can affect their effectiveness and safety in the considered pathology. This review article presents the results of major studies on the safety and effectiveness of different groups of beta blockers in various variants of long QT syndrome. The preferred beta-blockers for various genotypes of the syndrome were determined, and a comparative characteristic of beta-blockers for their safety and preventive effectiveness was given.